Efektivitas Teknik Restrukturisasi Kognitif Untuk Menangani Stres Akademik Siswa - Weni Kurnia Rahmawati (JKI (Jurnal Konseling Indonesia), 2016)
Academic stress is one type of stress as a result of instructional process or other stuff related to learning process. Several factors are known as the causes of the stress, such as the pressure to reach next grade, the amount number of task, the amount number of material, the target of minimum passing grade (KKM), bureaucracy, requirements to fulfill scholarships, desire to achieve a better career, exam anxiety and time management. The problem of the study is formulated as how is the effectiveness of cognitive restructuring technique to handle the students’ academic stress? The method applied in this study is quasi experimental study with single subject design which allows the researcher to determine the sample of the study based on certain criteria. The result of the study shows that t-value of hypothesis test was 6,084 with the level of sig. (2-tailed) = 0,000 with df = 7, so that the t-table = 1,895 at the significance level (α = 0,05). It is said that t value ≥ t table which was 6,084 ≥ 1,895. Sum up, it is concluded that the cognitive restructuring technique is effective in reducing the academic stress of the 7 graders of MTs Sardji Ar-Rasyid Dawuhan Situbondo. Keyword: Academic Stress, Cognitive Restructuring Technique